The Human Dimension in the Qur’anic Discourse Toward Non-Muslims: A Study in Light of the Concept of Mercy - Zainab Akram Qasim Mohsen, Asst. Lecturer (lark, 2026)
This study examines the human dimension of the Qur’anic discourse toward non-Muslims through an analytical approach based on the concept of mercy as a fundamental ethical and legislative principle in Islam. The research aims to demonstrate how the Qur’an addresses non-Muslims within a framework grounded in justice, tolerance, coexistence, and the preservation of human dignity, rather than exclusion or violence. The study relies on an analysis of relevant Qur’anic texts, supported by the Prophetic biography—particularly the model of the Conquest of Mecca—as well as the teachings of Ahl al-Bayt (peace be upon them), as reflected in Nahj al-Balagha and Al-Sahifa al-Sajjadiyya. These sources illustrate the moral and legal foundations governing relations between Muslims and others within Islamic society. The findings reveal that mercy constitutes the core value underlying the Qur’anic discourse toward non-Muslims, affirming that religious difference does not negate human rights, but rather necessitates peaceful coexistence, protection of life and property, and respect for covenants. The study also challenges prevailing stereotypes that portray Islam as a religion of violence, showing their inconsistency with both Qur’anic teachings and Islamic practice. The research recommends adopting a human-centered, objectives-based interpretation of the Qur’an to promote interfaith dialogue and social peace.